O processo de apropriação do gênero seminário por estudantes recém-ingressos no contexto universitário - Santos, Hermes Talles dos (2012)
The seminar, a discursive activity predominantly oral and a literacy practice, is a genre of discourse usually used in the academic community as a method of student assessment, which receives peculiar shapes, according to the area of knowledge that it takes place. In this context, first-year university students often participate in this activity intuitively. Based on the social-interactionist and socio-rhetorical language studies, and through qualitative research method we followed the oral presentations of new incoming undergraduate students, who belong to three distinct areas of knowledge (Agricultural Science, Exact Science and Humanities Science) of a public university in the State of São Paulo, with the purpose of examining how university students acquire the discursive seminar gender. By the analysis of audio and image recordings of the students‟ presentations, semi-structured interviews withteachers, field notes and journal, we concluded that students acquire this discursive activity based on oral presentations previously known or following other literacies practices presented in the academic context.